1958
DOI: 10.1017/s0022029900009547
|View full text |Cite
|
Sign up to set email alerts
|

739. The effect of heat treatment and temperature of storage on the yield, quality and chemical composition of karish cheese

Abstract: 1. Four batches of soft (Karish) cheese were made from raw and from heat-treated milk containing 1·5% fat and 7% added salt. The cheeses were sealed in tins in contact with their own whey and examined after storage for 1 month and 2 months at room temperature and at 4—6°C.2. Cheese stored at room temperature lost weight throughout the 2 months, but cheese stored at the low temperature gained weight after 1 month and lost weight after 2 months. Parallel changes occurred in the moisture content and salt content … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1958
1958
2020
2020

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 2 publications
0
1
0
Order By: Relevance
“…El-Sadek & Abd el Motteleb (2) found that heating milk to 170° C. for 15 min. before making into Karish cheese resulted in a higher yield of materially improved quality compared with that of cheese from raw separated milk.…”
Section: Introductionmentioning
confidence: 99%
“…El-Sadek & Abd el Motteleb (2) found that heating milk to 170° C. for 15 min. before making into Karish cheese resulted in a higher yield of materially improved quality compared with that of cheese from raw separated milk.…”
Section: Introductionmentioning
confidence: 99%